1998
DOI: 10.1038/sj.onc.1202017
|View full text |Cite
|
Sign up to set email alerts
|

Malignant transformation of NIH3T3 cells by overexpression of mot-2 protei

Abstract: The murine mortalin genes, mot-1 and mot-2, are members of the hsp70 family of proteins and di er from each other by only two amino acid residues. Mot-1 is expressed in normal cells and has pancytosolic cellular distribution whereas mot-2 is found in the perinuclear region of immortal cells. We report here that a high level of expression of mot-2 protein resulted in malignant transformation of cells as analysed by anchorage independent growth and nude mice assays. A high level of protein expression is attribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
79
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 15 publications
2
79
0
Order By: Relevance
“…The transcriptional activation function of p53 was impaired by transfections of mot-2, but not mot-1, protein suggesting a novel mechanism of p53 inactivation by mot-2 protein. In the present study, we demonstrate that mot-2 transformed NIH 3T3 cells [21] show inactivation and cytoplasmic sequestration of the p53 protein.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…The transcriptional activation function of p53 was impaired by transfections of mot-2, but not mot-1, protein suggesting a novel mechanism of p53 inactivation by mot-2 protein. In the present study, we demonstrate that mot-2 transformed NIH 3T3 cells [21] show inactivation and cytoplasmic sequestration of the p53 protein.…”
Section: Introductionsupporting
confidence: 60%
“…As expected mot-2 was expressed at a high level in NIH 3T3/mot-2 cells. p53 protein remained undetected in NIH 3T3/mot-2 cells by Western blotting implying that it is not mutated during the course of malignant transformation [21], [24]. NIH 3T3, its mot-2 derivative, normal mouse embryonic primary fibroblasts (CMEF) and its immortal mouse cell line, RS-4 that is shown to have mutant p53, were subjected to p53-responsive luciferase reporter assay along with p53-/-mouse embryonic fibroblasts.…”
Section: Resultsmentioning
confidence: 99%
“…Mot-2, a member of hsp70 family protein, was seen to interact with p53 and inactivate its transactivation function by abrogating its nuclear translocation [22]. While characterizing mouse fibroblasts stably transfected with mot-2, we found that in spite of inactivation of the p53 function by mot-2, these cells have high level of p21 WAF1 .…”
Section: Introductionmentioning
confidence: 81%
“…Mortalin is ubiquitously expressed, and so far has been detected in all mammalian cells analysed. This protein has been implicated in stress response (Ornatsky et al, 1995), muscle activity (Ibi et al, 1996), mitochondrial biogenesis (Schneider and Hood, 2000), control of cell proliferation (Kaul et al, 2000b), intracellular trafficking (Mizukoshi et al, 2001), differentiation (Xu et al, 1999) and tumorigenesis (Takahashi et al, 1994;Kaul et al, 1998;Wadhwa et al, 2006). Expression level of mortalin is frequently increased in tumours (Kaul et al, 2002;Dundas et al, 2005), where it is believed to cause inactivation of tumour suppressor protein TP53 .…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that the importance of such differences in mortalin localisation was also seen with the two isoforms (mot-1 and mot-2) of mouse mortalin. Indeed, overexpression of the pancytoplasmic mot-1 protein is sufficient to induce cell senescence in NIH 3T3 mouse fibroblasts (Wadhwa et al, 1993b), while introduction of the mot-2 perinuclear mortalin induced their malignant transformation Kaul et al (1998). Since mouse mot-1 and mot-2 isoforms differ only by two amino acids (Kaul et al, 2000a), it is tempting to speculate that in human, where there is only one mortalin isoform, this dual mortalin function is insured by the binding of mortalin to specific partners, such as CD9.…”
Section: Discussionmentioning
confidence: 99%